Mamamayan muna, hindi mamaya na [videorecording] - Philippines Civil Service Commission. Institute for Filipino Cinema; Aguilar, Mila D. ([S.l.] Institute for Filipino Cinema, 1994)
A government-wide campaign of the Civil Service Commission that addresses the need for behavioral reforms in the bureaucracy, particularly in the manner by which civil servants deal with the public
VHS.
Voice, Jess Dicolongon; Client, Ding Lucena, Numeriano Palocpoc, Kenneth Labrador; Bilis Aksiyon partner, Sherry Quiray; NGO Action Officer, Monina Tanseco-Lao; Secretary, Elaine Cedillo
Keywords: Civil service ethics -- Philippines; Philippines -- Officials and employees